Christliche Architektur in Ägypten - Grossmann, Peter. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2002)
This is the first comprehensive survey of Christian architecture in Egypt from the fourth century up to early modern times, covering not only church architecture, but also and extensively the building art of pilgrimage centers, monasteries, cemeteries, defence structures and private houses. Special attention is given to building technique, arrangement of the interior, and liturgical (local) conditions. With a descriptive catalogue of urban and monastic churches.